Three benefits of microcatheters for retrograde transvenous obliteration of gastric varices - Sonomura, Tetsuo (Baishideng Publishing Group Co., Limited, 2012)
AIM: To evaluate the usefulness of the microcatheter techniques in balloon-occluded retrograde transvenous obliteration (BRTO) of gastric varices. METHODS: Fifty-six patients with gastric varices underwent BRTOs using microcatheters. A balloon catheter was inserted into gastrorenal or gastrocaval shunts. A microcatheter was navigated close to the varices, and sclerosant was injected into the varices through the microcatheter during balloon occlusion. The next morning, thrombosis of the varices was evaluated by contrast enhanced computed tomography (CE-CT). In patients with incomplete thrombosis of the varices, a second BRTO was performed the following day. Patients were followed up with CE-CT and endoscopy. RESULTS: In all 56 patients, sclerosant was selectively injected through the microcatheter close to the varices. In 9 patients, microcoil embolization of collateral veins was performed using a microcatheter. In 12 patients with incomplete thrombosis of the varices, additional injection of sclerosant was performed through the microcatheter that remained inserted overnight. Complete thrombosis of the varices was achieved in 51 of 56 patients, and the remaining 5 patients showed incomplete thrombosis of the varices. No recurrence of the varices was found in the successful 51 patients after a median follow up time of 10.5 mo. We experienced one case of liver necrosis, and the other complications were transient. CONCLUSION: The microcatheter techniques are very effective methods for achieving a higher success rate of BRTO procedures.